Pedagogical Innovation in Moroccan Higher Education: Towards an Adaptation to the Demands of the 21st Century - NOUARI , Chaimae; BOUHAFS , Mounia (Revue Internationale du Chercheur, 2025)
Abstract: National and international changes have profoundly disrupted educational practices, particularly in higher education. The Moroccan university, like those around the world, must adapt to these new realities, taking into account the expectations of students and the requirements of the professional environment. Pedagogical innovation has emerged as a key lever for transformation, enabling the tackling of these challenges. It is now associated with ideas of modernity, growth, and reinvention. It embodies the evolution of educational practices and models, aiming to address current issues while anticipating the future needs of society. This article aims to clarify the concept of innovation, distinguishing it from invention, reform, and renovation. It explores pedagogical innovation by examining its different types, importance, and characteristics. Finally, it highlights recent transformations in Moroccan higher education and the models adopted to promote inclusive education.